2011
DOI: 10.1111/j.1365-2249.2011.04393.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of CD4+ T cell responses following splenectomy in hepatitis C virus-related liver cirrhosis

Abstract: SummaryDysfunction of T cells is a common feature in chronic persistent viral infections, including hepatitis C virus (HCV), and although hepatic and peripheral T cells have been studied extensively in chronic HCV hepatitis, the role of splenic T cell responses in such patients is poorly defined. This is an important issue, as thrombocytopenia is a complication of HCV-related liver cirrhosis (LC), due to splenic platelet sequestration and bone marrow suppression; splenectomy has been proposed to treat such pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 39 publications
2
41
0
Order By: Relevance
“…Splenic preservation would assist in maintaining the physiological functionality of T cells and as a consequence keep the optimal efficacy of check point inhibitors. [29][30][31][32][33][34][35] Our patient in this index report developed pneumonitis, an uncommon complication encountered with an antiprogrammed cell death receptor 1 (PD-1) or anti-programmed cell death ligand 1 (PD-L1) monoclonal antibody. However, drug-induced pneumonitis is a diagnosis of exclusion, and alternative diagnoses, including infection and malignancy, need to be sought first.…”
Section: Discussionmentioning
confidence: 99%
“…Splenic preservation would assist in maintaining the physiological functionality of T cells and as a consequence keep the optimal efficacy of check point inhibitors. [29][30][31][32][33][34][35] Our patient in this index report developed pneumonitis, an uncommon complication encountered with an antiprogrammed cell death receptor 1 (PD-1) or anti-programmed cell death ligand 1 (PD-L1) monoclonal antibody. However, drug-induced pneumonitis is a diagnosis of exclusion, and alternative diagnoses, including infection and malignancy, need to be sought first.…”
Section: Discussionmentioning
confidence: 99%
“…transforming growth factor (TGF)-β1, whereas others play an antifibrotic role, i.e. interleukin (IL)-10, interferon (IFN)-γ [3][4][5][6][7]. Moreover, HSCs with dual effects of antigenpresentation and collagen synthesis are recently reported to be involved in regulating CD4 + T cell responses [10,11].…”
Section: Introductionmentioning
confidence: 98%
“…Recently, accumulating evidence from mouse and human studies have emphasized the crucial role of infiltrating CD4 + T cells in the progression of liver inflammation and fibrosis [1,[5][6][7]. It has become clear that CD4 + T cells have heterogeneous effects for the existence of diverse functional subsets [1,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a splenectomy may not significantly increase the CD4 count before LT. However, Hashimoto et al reported that the CD4 function, in terms of IFN-gamma production and CD4 proliferation, increased after splenectomy (11). Accordingly, it is still controversial whether splenectomy should be performed before LT for patients with HIV infection in order to increase the number or function of CD4 cells.…”
mentioning
confidence: 99%